THE AUDIT OF THE FINANCIAL STATEMENTS DRAWN UP BY THE ENTITIES FROM TOURISM - Dorel Dumitru CHIRIȚESCU; Aurelia DUMITRU (Social Sciences and Education Research Review, 2019)
The audit represents a process developed by individuals or legal persons legally authorised, called auditors, within information regarding a certain entity is analysed and evaluated, profesionally. For this process specific techniques and procedures are being used, in order to obtain proofs, called audit evidence, based on them the auditors elaborate a paper, named audit report and they also provide a responsible and independent οріnіon, using evaluation criteria from the legal regulations or good practice unanimously recognized inside the field where the audited entity develops its activity (Mircea Boulescu, Marcel Ghiţă, Valerică Mareş – Audit Foundations, Didactic and Pedagogical Publishing House, Bucharest, 2005, page 11) The audit process, also called audit mission, is based on some national and international standards. Auditors are persons that get this quality under the conditions strictly ruled by the legislation in force. The audited entity can be a material/ an asset unity, the whole Government, ministries, departments, programmes, actions, transactions, operations; The audit represents the examination made by an independent and competent person regarding the fidelity of the accounting and financial presentasions and is the key for the probity and credibility of economic transactions.